WOMEN'S IMAGES IN THE WORK OF UZBEK AND RUSSIAN AUTHORS: FEATURES OF ARTISTIC EMBODIMENT - Kalonova Nargiza Nurzhovovna; Turdiyeva Iroda Choriyevna (Bright Mind Publishing, 2025)
The article is aimed at a comprehensive study of the semantic features of artistic comparisons used to form a woman. The most common thematic groups of comparisons characteristic of Russian and Uzbek literary traditions are highlighted, and analyzes their functional role in revealing the individuality and emotional and psychological depth of female characters. In addition, attention is paid to significant changes and transformations of the female image in different historical periods, which allows us to trace the evolution of ideas about women in these national literatures.
Keywords: Era, society, national traditions, education, the role of the mother and her image, artistic comparison, the image of women, the object of comparison.